Batimetría de la plataforma insular alrededor de la Isla del Coco, Costa Rica - Lizano R., Omar G. (2001)
The bathymetry of Coco’s Island (UNESCO Natural and Cultural World Patrimony), located approximately 500 km from the Pacific coast of Costa Rica, is not well known. It has a high marine biodiversity and also represents a meeting site for many species traveling throughout the Pacific Ocean. The insular shelf is irregular in extension and also in bathymetric features. The northeast limit is defined by the 109.8-128.1 m contours (60-70 fathoms) while the 183 m contour (100 fathoms) practically defines the rest of the island, from which the depth gradient is steep. The maximum extension is to the northeast with a longitude of 13 km. In this context the present limits of the marine park (5 km), are insufficient to protect the whole insular shelf. Current regulation should be modified to prevent fishing activities less than 15 km from the Island.